Regional powers, global aspirations: lessons from India and Iran - Fawcett, L; Jagtiani, S (Palgrave Macmillan, 2022)
This paper offers a revised and decentred perspective on regional power behaviour in world politics. Our revisionist approach departs from existing accounts by incorporating three key elements. First, in focusing attention on the regional-global nexus within which the international relations of regional powers have been conducted, demonstrating how regions can be mobilised as part of a status-seeking strategy at the global level. Second, examining this nexus historically: historical trajectories are vital sites of learning about the longstanding ambitions and policies of regional powers. Third, drawing on insights from critical geopolitics in highlighting the fluid and socially constructed nature of regions. We illustrate the interdependence of regional strategies and global outlooks through the cases of India and Iran, states in which we find parallels and shared insights demonstrating the value of a revisionist approach to analysing regional power behaviour, especially as their rise and growing capabilities inform a changing world order.